Study on the Mechanical Properties of Fly-Ash-Based Light-Weighted Porous Geopolymer and Its Utilization in Roof-Adaptive End Filling Technology - Luchang Xiong (Molecules, 2021)
This paper aims to study the porous structure and the mechanical properties of fly-ash-based light-weighted porous geopolymer (FBLPG), exploring the feasibility of using it in roof-adaptive end filling technology based on its in-situ foaming characteristics and plastic yielding performance. A porous structure model of FBLPG during both the slurry and solid period was established to study their influence factor. In addition, this study also built a planar structure model in the shape of a honeycomb with bore walls, proving that the bore walls possess the characteristics of isotropic force. FBLPG shows a peculiar plastic yielding performance in the experiment where its stress stays stable with the gradual increase of the deformation, which can guarantee the stability of a filling body under the cycled load from the roof. At the same time, the in-situ foaming process combined with the unique filling technique can make the FBLPG filling body fully in contact with the irregular roof. This roof-adaptive end filling technology makes it a successful application in plugging the 1305 working face, which avoids problems of the low tight-connection ratio and secondary air-leakage channel resulted from the traditional filling technology, effectively improving coal production in terms of safety and high efficiency.